The universality of the petition in the light of its 2014 regulation (Discourse of Law and Administration, 2022)
Petition, after adopting the Constitution in 1997, hadn’t been specifically regulated in the statutory law for a long time, with the exceptions of Administrative Procedure Code and Senate Human Rights, Rule of Law and Petition committee. It changed in 2014, when the Petition Act was passed. The institution of petition, in order to assure not only direct communication with the authorities on many fields, but give the meaning of influencing the state affairs as well, needs to have both wide subjective and material scope. The author analyzes its elements in the aforementioned act as well as indicates how it could be improved.
Keywords: petition; constitution; human rights; political rights